UTILIZATION OF ZIRCON FROM THE BY-PRODUCT OF TIN MINING AS CATALYSTS SUPPORT FOR STEAM REFORMING OF METHANOL - Widiastri, Meta
ZrSiO4 (zircon) is one of the by-product of tin mining. ZrSiO4 potention as a catalyst support was never been discovered before. In this research, Cu/ZrSiO4 was synthesized with incipient wetness impregnation method for steam reforming of methanol reaction. Catalysts that have been synthesized was Cu/ZrSiO4 with 9% and 15% Cu-mole (9%Cu/ZrSiO4 and 15%Cu/ZrSiO4); Cu/ZrSiO4 catalysts with different calcination temperature (300oC and 500oC); and 15%Cu/15%ZnO/ZrSiO4 catalyst. Characteristic and activity of the catalysts were compared to LTSC (Low Temperature Shift Conversion) commercial catalyst (Cu/ZnO/Al2O3). Steam reforming of methanol catalyzed by those catalyst at 300oC showed methanol conversion of 15% for 9%Cu/ZrSiO4, 28% for 15%Cu/ZrSiO4, 4% for 15%Cu/ZrSiO4 (Tcalcination = 300oC), and 21% for 15%Cu/15%ZnO/ZrSiO4. XRD diffractograms show that the catalysts are crystalline. The BET measurement results shows that specific surface area are 4.94 m2/g for ZrSiO4, 5.58 m2/g for 15%Cu/ZrSiO4, and 2.74 m2/g for 15%Cu/15%ZnO/ZrSiO4.